PENGARUH MODAL MANUSIA, MODAL STRUKTURAL, DAN MODAL PELANGGANTERHADAP KINERJA BISNIS - WAHYUNI MARDIANA, ITA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract:This study aims to analyze the implementation effect of human capital, structural capital, and customer capital to business performance (Study on SMEs in Surabaya). The dependent variable in this study is business performance and the independent variable is human capital, structural capital, and customer capital. The data in this study consist of the primary data that taken from questionnaires distributed directly to the 52 respondents from SMEs in Surabaya. The hypothesis in this study were analyzed using analysis techniques of multiple linear regression analysis with the help of software SPSS 16.0 for Windows.The results of this research showed that human capital, structural capital, and customer capital have positive and significant impact on business performance, meanwhile intellectual capital (human capital together with customer capital and structural capital) have positive and significant impact on business performance. Keywords: intellectual capital, human capital, structural capital, customer capital, and business performance.